2011
DOI: 10.1088/0953-8984/24/5/052206
|View full text |Cite
|
Sign up to set email alerts
|

Localized 5f electrons in superconducting PuCoIn5: consequences for superconductivity in PuCoGa5

Abstract: The physical properties of the first In analog of the PuMGa(5) (M = Co, Rh) family of superconductors, PuCoIn(5), are reported. With its unit cell volume being 28% larger than that of PuCoGa(5), the characteristic spin-fluctuation energy scale of PuCoIn(5) is three to four times smaller than that of PuCoGa(5), which suggests that the Pu 5f electrons are in a more localized state relative to PuCoGa(5). This raises the possibility that the high superconducting transition temperature T(c) = 18.5 K of PuCoGa(5) st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 38 publications
(50 reference statements)
1
72
0
1
Order By: Relevance
“…Fortunately, the FEFF code (version 9.6.4) is capable of demonstrating the role of f orbital delocalization in contributing to shifts in the threshold energy [40,41]. Figure 6 shows the results from such ab initio calculations using the nominal crystal structures [26,27,42,43,44] and mostly default values for running the code, with a few exceptions. The cluster radius was chosen to be 6Å after finding that the calculations for all samples were converged using this size.…”
Section: Pfy Measurements and Feff Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, the FEFF code (version 9.6.4) is capable of demonstrating the role of f orbital delocalization in contributing to shifts in the threshold energy [40,41]. Figure 6 shows the results from such ab initio calculations using the nominal crystal structures [26,27,42,43,44] and mostly default values for running the code, with a few exceptions. The cluster radius was chosen to be 6Å after finding that the calculations for all samples were converged using this size.…”
Section: Pfy Measurements and Feff Calculationsmentioning
confidence: 99%
“…We will expound on those results below and outline some improved analysis techniques that are applied to the previous RXES data, as well as to data from two new samples, the Pu-based 115 superconductors, PuCoGa 5 [26] and PuCoIn 5 [27].…”
Section: Introductionmentioning
confidence: 99%
“…There is not enough specific heat data to really make a good comparison between the materials based on this, but the comparison of lattice volumes for the two in relation to the volumes of the corresponding rare earth materials is interesting and gives support to the idea that these two compounds may be in different regimes (Fig. 10) [28]. It is known that the actinide elements when their 5f's become fully localized have volumes which lie close to those of the cor- responding rare earth elements.…”
mentioning
confidence: 99%
“…It was recently reported that PuIn 3 has a possible antiferromagnetic ordering at 14 K [3]. Although the details of the ordering have not been clarified, one can assume a modification of the Brillouin zone in the ordered state.…”
Section: Experiments and Discussionmentioning
confidence: 99%